KEANEKARAGAMAN TUMBUHAN HERBA DAN PERDU PADA JALUR PENDAKIAN LEMBAH RAMMA DI GUNUNG BAWAKARAENG KABUPATEN GOWA - Musyawir Musyawir; Andi Nur Samsi; Ahmad Hasyim (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2021)
This research was conducted in July-September 2018 on the track of the Ramma valley on Mount Bawakaraeng, Gowa Regency from July to September 2018. The type of research used is descriptive quantitative. Observation using transects made 20 plots measuring 2x2 meters. Species samples in the plot were taken and then photographed and identified. This study aims to determine the types and diversity of cover plants (herbs and shrubs) found in the Ramma Valley climbing route on Mount Bawakaraeng, Gowa Regency. The research found 24 species consisting of 19 herbs and 5 shrubs. The diversity index (H ') of herb plants is 2.451 which is moderate, for shrubs it is 1.379 which is low.